The Effectiveness of Lyubomirsky’s Happiness Training on Negative Emotions (Depression, Stress, and Anxiety) and Cognitive Flexibility in Mothers of Children with Autism Spectrum Disorder - Mahjoor, Fatemeh; Fazeli Mehrabadi, Alireza (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to investigate the effectiveness of happiness training based on Lyubomirsky’s model in reducing negative emotions and enhancing cognitive flexibility in this population. Methods and Materials: This study employed a quasi-experimental design using a pretest-posttest control group format. The statistical population included mothers of children with autism who attended the "Golhaye Beheshti" Center in Qom during spring 2024. A total of 30 participants were selected through simple random sampling and assigned to either the experimental or control group. The experimental group participated in eight 90-minute sessions of happiness training. The research instruments included the Depression, Anxiety, and Stress Scale (DASS-21) and the Cognitive Flexibility Scale developed by Dennis and Vander Wal (2009). Data were analyzed using analysis of covariance (ANCOVA). Findings: The results indicated that Lyubomirsky’s happiness training significantly reduced depression, anxiety, and stress levels while significantly increasing cognitive flexibility in the experimental group (P < 0.05). Conclusion: Happiness-based intervention can serve as an effective strategy for promoting the mental health of mothers of children with autism by alleviating negative emotions and strengthening their cognitive capacities. Keywords: Happiness training, depression, anxiety, stress, cognitive flexibility, mothers, autism spectrum disorder.